BUILDING AN EARTHQUAKE EARLY WARNING SYSTEM IN INDONESIA: LESSONS LEARNED FROM MEXICO - Ahmad Fatkul Fikri; Rustian Rustian; Prasetio Wijaksono; Gita Yulianti Suwandi; Catur Susilo Rahardi; Andi Kurniawan (Jurnal Kebijakan Publik, 2026)
Indonesia and Mexico have similar earthquake disaster risk characteristics. These two countries will experience only small losses from earthquakes if they have the effective management system. Mexico has established itself as one of exceptional early earthquake warning system through a learning process. The country is able to reduce the number of disaster victims significantly in recent years. In this regard, this research attempts to explore Mexico’s experience in disaster management and the valuable lessons for potential earthquake preparedness in Indonesia. To gain a comprehensive pictures of public policy’s efforts in mitigating the earthquake risks in both countries, the research has used a qualitative approach especially through focus group discusssions participated by key stakeholders including professors, researchers, and relevant practicioners from both countries. In addition, the research also optimizes the use secondary sources, policy documents and international academic publications, to strengthen our analysis. The study has discovered several critical factors behind Mexico’s significant capability to reduce the earthquake risks. These include the strong public awareness of earthquake, where people are more alert towards signals and indications of the catastrophe, the country’s effort in advancing the monitoring and warning technology through the development of algorithms and cross-agency collaborations. It is also combined with extensive facilities to dessiminate and communicate effectively the early warning to cover all public areas, and the robust government’s support in encouraging routine public simulation of earthquake disaster, also involving the large corporations. In conclusion, the study argues that these Mexico’s practical experiences could enrich Indonesia’s disaster management strategies particularly through fostering the early warning system technology, enhancing public preparedness, and strong cross-agency collaboration in strengthening monitoring and warning system.